Kebakaran hutan dan isu pencemaran udara di Malaysia: kes jerebu pada Ogos 2005 - Shaharuddin Ahmad,; Noorazuan Md Hashim, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2006)
Air pollution in Malaysia, particularly the haze episode, has a strong relationship with the existence of hot spots observed from satellite image of Sumatra Island, Indonesia. Previous studies have shown that longer periods of dry spell due to El-Niño phenomenon and the open burning practices of the agriculture areas of Sumatra triggered the haze episode in Malaysia. This article attempts to analyse the haze hazard on human and natural environments in Malaysia by focusing on the haze episode of August 2005. Using the GIS contour technique, the distribution of haze concentration or suspended particulate of the size smaller than 10 microns (PM10) was plotted for Peninsular Malaysia. Analysis of satellite data NOAA-14 from June to August 2005 showed that there were more than 250 hot spots within the burning green coverage areas in East Sumatra. The haze episode on the west coast of Peninsular Malaysia worsened with the weak south-west wind. This preliminary result shows that there is a variation in air pollution concentration trends due to changes in the direction and speed of south-west prevailing wind during the haze episode. It is hoped that this study will provide the basic information for haze episode modelling in future, especially the impact of haze on primary economy sectors of Malaysia